Incivility in nursing education: A systematic literature review. (August 2019) - Eka, Ni Gusti Ayu; Chambers, Derek
Abstract: Incivility has been investigated worldwide in various settings including non-health and health care settings. However, it has become a growing concern in higher education including nurse education. This is particularly disconcerting since it is concerned with developing a caring profession. This systematic literature review aims to describe perceptions of students and members of faculty regarding incivility in nursing education. It identifies and discusses gaps in the literature and the need for future studies. This review was part of a doctoral thesis to which more recent studies have been added. A systematic literature review was conducted using the following steps: identification of a research question, data searching, data selection and data analysis. The approach was conducted to provide clear systematic steps and accommodate varied methods. Four themes emerged from the analysis including: (i) perceived instances of incivility; (ii) factors related to incivility; (iii) the impact of incivility, and (iv) strategies for promoting civility in nursing education. The study also identifies the need for randomised-intervention studies that investigate the phenomena.